Social power of preadolescent children on influence in their mothers' purchasing behavior: Initial study in Peruvian toy stores - Miriam Carrillo; Alicia Gonzalez-Sparks; Nestor U. Salcedo (Journal of Economics, Finance and Administrative Science, 2018)
This paper aims to investigate the relationship between legitimate and expert social power types of preadolescent children on the influence perception in their mothers' purchasing behavior in Peruvian toy stores. The literature review takes into consideration the concepts of social power and the influence on family behavior to then focus on social power within family behavior with the of mainly developing four hypotheses regarding purchasing behavior. Design/methodology/approach The methodology followed a non-experimental transversal correlational-causal design. A pilot sample size of 67 cases was used. The sample was based on an objective population of Peruvian mothers of families that live in northern Lima and that go to purchase toys to major shopping centers with their children aged 8-11 years. Findings The results show that the expert social power, as well as the legitimate social power, has a strong relationship. In addition, both social powers have an impact on the influence perception in purchasing child-mother, but not on the influence perception in purchasing mother-child. Moreover, the test of moderation of the expenditure level on toy purchases did not have an effect on the context that was studied. Originality/value The contribution shows that important changes are happening in the consumption behavior on the aspect of children influencing mothers, and that for Latin American contexts, the level of expenditure still does not crucially affect the causality demonstrated.
Keywords: 330; Expert social power; Influence in purchasing behavior; Legitimate social power; Peruvian toy stores